Determining Determining the award of scholarships using the profil matching method at SMP SAnto Markus II: Penentuan Pemberian Beasiswa Dengan Menggunakan Metode Profil Matching Pada SMP Santo Markus II - Vivi Okta Siringoringo; saghifa Fitriana (Informatics and Computer Engineering Journal, 2021)
Scholarships are one work program that is almost in every educational institution. This scholarship program aims to ease the burden on students in taking up education, especially in matters of cost. SMP Santo Markus II is one of the institutions engaged in education. This study uses Profile Matching method in determining the case for middle school. The assessment aspects used are academic aspects, personality aspects and family economic aspects. The results of this study resulted in a ranking sequence of prospective students receiving scholarships that have been selected, thus helping the school in determining who students are selected as scholarship recipients. Data processing using Microsoft Excel 2010.